The Frequency of Allergic Rhinitis among Obstructive Sleep Apnea Patients: A Hospital-Based, Cross-Sectional Study - Ghada u. Gadi,; Mohammad H. Albar,; Abdulkareem R. Fida,; Khalil S. Sendi,; Khaled I. Alnoury,; Siraj O. Wali, (Journal of King Abdulaziz University: Medical Sciences, 2023)
A relationship between obstructive sleep apnea and allergic rhinitis is controversial. Allergic rhinitis may potentially worsen severity of sleep apnea and hence, treating allergic rhinitis may actually improve sleep apnea as well as habitual snoring. Our aim was to determine the prevalence of allergic rhinitis among obstructive sleep apnea patients. In this cross-sectional study, all patients were referred to the Sleep Clinic at King Abdulaziz University Hospital from February to August 2013 and agreed to participate in the study were recruited. The diagnosis of obstructive sleep apnea was based on Berlin questionnaire followed by confirmatory Polysomnography. Allergic rhinitis was confirmed via focused history and clinical examination. Seventy adults were recruited, with mean age of 49.3 ± 13.42 years, and mean body mass index of 38.5 ± 12.63 kg/m2. 54 (77.14%) patients were diagnosed to have obstructive sleep apnea, 26 (48%) of them had allergic rhinitis. No significant association was found between allergic rhinitis and severity of obstructive sleep apnea (p-value < 0.05). In conclusion, the prevalence of allergic rhinitis among obstructive sleep apnea patients was found to be 48.15%, with no clear correlation to the severity of obstructive sleep apnea.